2020
DOI: 10.1177/2055217319848467
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting MS patients’ health-related quality of life and measurement challenges in Lebanon and the MENA region

Abstract: Background In the Middle East and North Africa (MENA) region, few studies explored the quality of life of multiple sclerosis patients and the factors affecting it. Objective The objective of this study was to explore studies on multiple sclerosis quality of life in the MENA area through a comprehensive literature review. To validate the Multiple sclerosis international Quality of Life (MusiQoL) and Modified Fatigue Impact Scale (MFIS) in Arabic, and investigate the impact of sociodemographic and clinical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
8
13
1
Order By: Relevance
“…In our study, the highest self-rated quality of life concerned RFa (81.37), RFr (69.83), and REJ (69.04) domains. In contrast, the lowest quality of life was reported regarding COP (51.72) and PWB (55.67), which is consistent with the results obtained by Koltuniuk et al 79 among female MS patients and Farran et al 76 On the other hand, in the validation study of the Polish version of the MusiQoL questionnaire, MS patients scored significantly lower on average – 42.5 points, and they rated their quality of life highest in terms of SPT and lowest in RFa. This difference is likely because all patients included in our study suffered from RRMS and were participating in a drug program that translates into better functional ability and the capacity to participate in family and work-life more actively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the highest self-rated quality of life concerned RFa (81.37), RFr (69.83), and REJ (69.04) domains. In contrast, the lowest quality of life was reported regarding COP (51.72) and PWB (55.67), which is consistent with the results obtained by Koltuniuk et al 79 among female MS patients and Farran et al 76 On the other hand, in the validation study of the Polish version of the MusiQoL questionnaire, MS patients scored significantly lower on average – 42.5 points, and they rated their quality of life highest in terms of SPT and lowest in RFa. This difference is likely because all patients included in our study suffered from RRMS and were participating in a drug program that translates into better functional ability and the capacity to participate in family and work-life more actively.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also shown a link between socio-demographic variables and specific domains of quality of life in MS patients. 64 , 76 , 77 For instance, age is negatively correlated with the MusiQoL total score, 76 which was also confirmed in our study. Jamroz-Wisniewska et al 64 and Nickel et al 77 showed that males rated the quality of life in PWB higher than females, which was also confirmed by our study.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, there was a statistically significant inverse relationship between change in EDSS score over time and change in MusiQoL total score, with a 1-point increase in EDSS score associated with a 1.44 ( p = 0.0003) point decrease in MusiQoL total score. These observations were similar to a study assessing HRQoL in the Middle East and North Africa region which found that a higher EDSS scores was associated with a lower MusiQoL score [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…At baseline, the mean MusiQoL total score was 65.67 ± 0.8 demonstrating that overall, the patients' mostly assessed their quality of life positively. These positive perceptions of HRQoL were also observed in a MusiQoL study conducted in Lebanon [ 9 ].…”
Section: Discussionsupporting
confidence: 64%
“…Adapting and validating questionnaires for the measurement of quality of life or fatigue is an area of active development as reported by Farran et al, 17 in which the authors were able to validate the Arabic multiple sclerosis international quality of life (MusiQoL) and modified fatigue impact scale (MFIS). Their data showed that quality of life was impacted by psychosocial fatigue in addition to age and disease type.…”
mentioning
confidence: 99%